2013
DOI: 10.1371/journal.pone.0055135
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Specific Mechanisms of IGF1R Inhibition by Ganitumab

Abstract: BackgroundTherapeutic antibodies targeting the IGF1R have shown diverse efficacy and safety signals in oncology clinical trials. The success of these agents as future human therapeutics depends on understanding the specific mechanisms by which these antibodies target IGF1R signaling.Methodology/Principal FindingsA panel of well-characterized assays was used to investigate the mechanisms by which ganitumab, a fully human anti-IGF1R antibody undergoing clinical testing, inhibits IGF1R activity. Epitope mapping u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Heterodimers of IGF1R/IR are preferentially activated by IGF ligands; therefore, treatment with anti-IGF therapies would also impact IGF1R/IR receptor activity. For example, ganitumab (AMG 479), a monoclonal antibody against IGF1R, has been shown to be effective against inhibiting IGF ligand stimulated activation of IGF1R/IR heterodimers [ 77 ],[ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heterodimers of IGF1R/IR are preferentially activated by IGF ligands; therefore, treatment with anti-IGF therapies would also impact IGF1R/IR receptor activity. For example, ganitumab (AMG 479), a monoclonal antibody against IGF1R, has been shown to be effective against inhibiting IGF ligand stimulated activation of IGF1R/IR heterodimers [ 77 ],[ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mouse monoclonal antibody to human IGFIR-MAb 391 (R&D Systems; ref. 29) was used to treat tumor-bearing mice in vivo. For IHC, rabbit polyclonal antibodies to pIGFIR, Ki67, and cleaved caspase-3 (all from Abcam) and a rat monoclonal antibody to CD31 (Clone MEC 13.3) from BD Biosciences were used.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Binding of ligands, IGF-1 or IGF-2, leads to a conformational change and autophosphorylation of the receptor, which activates downstream signaling pathways such as the PI3K/Akt and the Ras/Raf/MEK/ERK pathways. These pathways are shown to inhibit apoptosis, and improve cell survival, cell proliferation and invasion 28, 29 . IGF-1R, IGF-1 and IGF-2 are overexpressed in PDAs and preclinical studies have shown that the IGF-1R signaling cascade plays a pro-oncogenic role 30 .…”
Section: Current Monoclonal Antibody Therapies For Pda Treatmentmentioning
confidence: 99%